2013
DOI: 10.1587/transinf.e96.d.176
|View full text |Cite
|
Sign up to set email alerts
|

Current and Future ITS

Abstract: Intelligent Transport System (ITS), aiming to provide innovative services related to traffic management, road safety and convenience, has drawn much attention in academic and industrial worlds in recent years. Japan has been considered as an advanced country in ITS development. This paper first gives an overview of the current ITS operated in Japan including Vehicle Information and Communication System (VICS), Electronic Toll Collection System (ETC), and ITS-spot system. Then this paper introduces the trends a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Sai et al [7] reported the development of a current and future intelligent transportation system (ITS) in which the safety initiatives included preventing traffic crashes via cooperation between vehicles based on road infrastructure. Ito et al [8] analyzed the differences between side-impact car-and-cyclist crashes and near crashes based on an analysis of driving recorders.…”
Section: Related Workmentioning
confidence: 99%
“…Sai et al [7] reported the development of a current and future intelligent transportation system (ITS) in which the safety initiatives included preventing traffic crashes via cooperation between vehicles based on road infrastructure. Ito et al [8] analyzed the differences between side-impact car-and-cyclist crashes and near crashes based on an analysis of driving recorders.…”
Section: Related Workmentioning
confidence: 99%
“…Intelligent vehicle (IV) is an important part of intelligent transportation system (ITS), 1 3 which is carried with advanced vehicular sensors, controllers, and actuators and combined with modern communication and network technology. It is equipped to conduct road environment perception, 4 path planning, 5 and automatic control.…”
Section: Introductionmentioning
confidence: 99%
“…As the rapid integration of new generation information technology, sensor, intelligent control and automotive products, intelligent automobile technology has become one of the hot researches in today's automobile engineering [1, 2]. Its critical issues lie in perception, motion planning and control [3, 4].…”
Section: Introductionmentioning
confidence: 99%